State and perspectives of gastronomic tourism in Bosnia and Herzegovina case of Herzegovina region - Vukojevic, Dajana; Berjan, Siniša; El Bilali, Hamid (Turizam, 2021)
Gastronomic tourism represents an important aspect in tourism environment and is often a central segment of the tourist experience. The paper aims at analysing gastronomic tourism offer in Herzegovina region (Bosnia and Herzegovina), taking into consideration its natural and cultural characteristics, and provide recommendation for its improvement. Primary data were collected by face-to-face interviews carried out with rural tourism stakeholders viz. managers of tourist organizations, owners of catering facilities, winery owners, local food producers and visitors (tourists). Research was conducted in July 2019 in seven cities and/or municipalities of Herzegovina region (Mostar, Trebinje, Capljina, Ljubuski, Bileca, Nevesinje and Gacko).The first part of the paper illustrates Herzegovina as a destination rich in natural and cultural attractions with a focus on traditional cuisine. In the second part, based on the research results, the situation is assessed and recommendations for the future development of gastronomic tourism are given in order to improve the existing tourist offer. Many actors in tourism (e.g. hotels, restaurants, local community, etc.) have realized the importance of gastronomy as a catalyst for the movement of tourists and stimulation of local, regional and national economic development. Typical products, such as domestic food and wine, have been given an adequate function to characterize the tourist offer and represent in many cases the main attraction. ​​Herzegovina region is recognizable by its traditional cuisine, which represents an important asset for the future development of gastronomic tourism. Education and raising the awareness of all actors as well as local communities about gastronomic tourism is paramount for sector development. Local entrepreneurial endeavours can benefit from connection and exchange with partners from Europe to create a recognizable gastronomic destination in the tourism market. Furthermore, technical and financial support to gastronomic tourism operators is crucial in this stage of its development.
Keywords: Tourism, gastronomy, gastronomic tourism, Herzegovina region, Bosnia and Herzegovina, rural tourism, sustainable development.